Development and Validation of Spectrophotometric Methods for the Estimation of Itraconazole - Murthy, T.K.; Reddy, M.N.; Srinivasa Rao, Y.; Srinivasu, K.; Sankar, D.G. (Asian Journal of Chemistry, 2010)
Three simple spectrophotometric methods (A, B and C) have been developed for the determination of itraconazole in pure and in its pharmaceutical formulations. Method A is based on the formation of blood red colored complex with ferric chloride and 2,2' -bipyridine having absorption maximum at 525 nm. In method B, itraconazole forms green coloured complex with ferric chloride and potassium ferricyanide exhibiting maximum absorption at 725 nm, whereas method C is based on the oxidation of the drug with a known excess of oxidant. potassium permanganate (KMnO4). The excess permanganate is determined using the dye, Fast Green FCF (FGFCF) at 625 nm. The results obtained are reproducible and are statistically validated.